Healthcare resource utilization and quality of life in patients with sarcoidosis‐associated pulmonary hypertension. (30th September 2022) - Lawrie, Allan; Hamilton, Neil; Wood, Steven; Exposto, Fernando; Muzwidzwa, Ruvimbo; Raiteri, Louise; Beaudet, Amélie; Muller, Audrey; Sauter, Rafael; Pillai, Nadia; Kiely, David G.
Abstract: A retrospective, observational cohort study was conducted to generate real‐world evidence in adult patients diagnosed with sarcoidosis‐associated pulmonary hypertension (SAPH) at a referral center in England between 2012 and 2019. Data from the referral center electronic medical record database were linked to the National Health Service Hospital Episode Statistics database to collect and analyze patient demographics, clinical characteristics, comorbidities, treatment patterns, health‐related quality of life (HRQoL; assessed using the EmPHasis‐10 questionnaire), healthcare resource utilization (HCRU), costs, and survival. Sixty‐two patients with SAPH were identified. At diagnosis, 84% were in WHO functional class III and presented with significant pulmonary hemodynamic impairment. Cardiovascular and respiratory comorbidities were commonly reported prediagnosis. Median EmPHasis‐10 score at diagnosis was 34, indicative of poor HRQoL. In the 1st year after diagnosis, median (Q1, Q3) per‐patient HCRU was 1 (0, 2) all‐cause inpatient hospitalizations; 3 (2, 4) same‐day hospitalizations; and 9 (6, 11) outpatient consultations. In 24 patients who were hospitalized longer than 1 day in the 1st year after diagnosis, the median duration of hospitalization was 4 days. With a median follow‐up of 1.8 years, the median overall survival was 2.9 years. In this cohort of patients with SAPH, poor HRQoL and high HCRU were observed following diagnosis. To our knowledge, this is the first study to report on HRQoL and HCRU in patients with SAPH. More research is needed on treatment options for this population with high unmet needs.